Long Electron−Hole Separation of ZnO-CdS Core−Shell Quantum Dots - Xu, Fen; Volkov, Vyacheslav; Zhu, Yimei; Bai, Hanying; Rea, Anthony; Valappil, Nikesh V; Su, Wei; Gao, Xueyun; Kuskovsky, Igor L; Matsui, Hiroshi (Journal of physical chemistry. C, 2009)
The tunability of electronic and optical properties of semiconductor nanocrystal quantum dots (QDs) has been an important subject in nanotechnology. While control of the emission property of QDs in wavelength has been studied extensively, control of the emission lifetime of QDs has not been explored in depth. In this report, ZnO-CdS core−shell QDs were synthesized in a two-step process, in which we initially synthesized ZnO core particles, and then stepwise slow growth of CdS shells followed. The coating of a CdS shell on a ZnO core increased the exciton lifetime more than 100 times that of the core ZnO QD, and the lifetime was further extended as the thickness of shell increased. This long electron−hole recombination lifetime is due to a unique staggered band alignment between the ZnO core and CdS shell, so-called type II band alignment, where the carrier excitation holes and electrons are spatially separated at the core and shell, and the exciton lifetime becomes extremely sensitive to the thickness of the shell. Here, we demonstrated that the emission lifetime becomes controllable with the thickness of the shell in ZnO-CdS core−shell QDs. The longer excitonic lifetime of type II QDs could be beneficial in fluorescence-based sensors, medical imaging, solar cells photovoltaics, and lasers.